IMPLEMENTASI METODOLOGI WATERFALL DALAM SISTEM PENDUKUNG KEPUTUSAN PENYEDIA INFORMASI AKADEMIK UNIVERSITAS - Dian Ambar Wasesha (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2019)
Academic information systems at the University are only able to support operational activities but have not been able to provide specific reports needed by the leaders. The system development method used is waterfall model which consists of four stages. System that will be developed is aims to make it easier for leaders to obtain information about academic activities. So that later, total student growth and total growth of graduating students by year can be monitored well. Likewise, total of active, non-active and drop-out students can be known quickly. The data can be used to assist the decision making process.